Effects of fasting and refeeding on somatostatin concentration and binding to cytosol from rabbit gastric mucosa. Issue 5 (May 1988) - Roca, B; Fernandez-Valencia, R; Arilla, E
Abstract : Somatostatin like immunoreactivity and the density of somatostatin binding sites were measured in stomach (fundus and antrum) from either fed, 12 to 96 hours fasted, or 96 hours fasted plus 48 hours refed rabbits. The somatostatin concentration increased in fundic and antral mucosa after 24 h and reached its highest value after 96 h of fasting. The number of specific somatostatin binding sites with high and low affinity decreased with the duration of fasting. Refeeding of fasted animals resulted in a normalisation to control values of gastric mucosal somatostatin and somatostatin binding.